Business Intelligence Dashboard of Food Sales Based on Key Performance Indicator Case Study: Xyz Cinema - Aditiya Hermawan; Kevin Ivone Sim (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Business competition is getting tougher along with the development of information technology. Information technology helps businesses to accelerate in everything, for example sales. The growing sales data makes the data more and more every day. This is a problem for companies to be able to manage data and retrieve information quickly and accurately. To support this we need several tools that can help manage data to support ongoing business processes. A Business Intelligence dashboard that uses a Business Intelligence Roadmap and Key Performance Indicator (KPI) can make it possible to analyze data quickly, according to the needs and targets the company wants to achieve. From this research, produce an application that makes it easy for users to analyze and monitor sales activities and can also find out sales trends easily. So that it allows users to set strategies to increase sales.